Analysis of an energy storage sizing for grid-connected photovoltaic system - Aimie Nazmin Azmi; Norhafiz Salim; Aziah Khamis (Institute of Advanced Engineering and Science, 2019)
This paper present on the analysis of an energy storage sizing for a small grid-connected PV system. This project is to study the proper sizing of energy storage (battery) in a grid-connected PV system for consumers whom purchase and sell electricity from and to the utility grid. The goal is to minimize the total cost of the operation for a consumer with a PV system with a battery storage system. This is to make sure that minimizing the total annual operating cost while maintaining an efficient system. This study uses typical consumer load consumption, and solar irradiance data throughout a year, while varying the type of battery storage (study lead acid and Lithium ion battery) as an energy storage for a similar system. Since lithium ion is not the main options to be integrated with PV system, this study will then reveal the data in terms of cost on why it is not a popular choice.